New Complex Hyperbolic Structures to the Lonngren-Wave Equation by Using Sine-Gordon Expansion Method - Baskonus, Haci Mehmet; Bulut, Hasan; Sulaiman, Tukur Abdulkadir (Walter de Gruyter Gmbh, 2019)
In this paper, a powerful sine-Gordon expansion method (SGEM) with aid of a computational program is used in constructing a new hyperbolic function solutions to one of the popular nonlinear evolution equations that arises in the field of mathematical physics, namely; longren-wave equation. We also give the 3D and 2D graphics of all the obtained solutions which are explaining new properties of model considered in this paper. Finally, we submit a comprehensive conclusion at the end of this paper.
Keywords: The sine-Gordon expansion method; the longren-wave equation; hyperbolic function solutions